2020
DOI: 10.1016/j.ebiom.2020.102651
|View full text |Cite
|
Sign up to set email alerts
|

MiR-18a-downregulated RORA inhibits the proliferation and tumorigenesis of glioma using the TNF-α-mediated NF-κB signaling pathway

Abstract: Background: Glioma has a poor prognosis, and is the most common primary and lethal primary malignant tumor in the central nervous system. Retinoic acid receptor-related orphan receptor A (RORA) is a member of the ROR subfamily of orphan receptors and plays an anti-tumor role in several cancers. Methods: A cell viability assay, the Edu assay, neurosphere formation assay, and xenograft experiments were used to detect the proliferative abilities of glioma cell line, glioma stem cells (GSCs). Western blotting, ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 48 publications
0
80
0
Order By: Relevance
“…The hBMECs were maintained in endothelial cell medium (ECM; ScienCell Research Laboratories). Six patient-derived primary glioma stem cells from WHO grade II to IV (grade II: GSC205 and GSC207; grade III: GSC306 and GSC307; grade IV: GSC406 and GSC408) were isolated, and neurosphere cultures were obtained as previously described [23]. The detailed clinicopathological information is presented in Table S2.…”
Section: Cell Culture and Gscs Isolationmentioning
confidence: 99%
See 3 more Smart Citations
“…The hBMECs were maintained in endothelial cell medium (ECM; ScienCell Research Laboratories). Six patient-derived primary glioma stem cells from WHO grade II to IV (grade II: GSC205 and GSC207; grade III: GSC306 and GSC307; grade IV: GSC406 and GSC408) were isolated, and neurosphere cultures were obtained as previously described [23]. The detailed clinicopathological information is presented in Table S2.…”
Section: Cell Culture and Gscs Isolationmentioning
confidence: 99%
“…The sequences of all siRNAs are listed in Table S3. The lentivirus transfection and efficacy measurements were performed as previously described [23].…”
Section: Lentiviral Vector Construction and Transfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 miR-18a has a promoting effect on glioma via inhibiting retinoic acid receptor-related orphan receptor A (RORA) and activating the TNF-α mediated NF-κB signaling pathway. 17 Recent studies showed that the biological activity of TSN was related to miRNAs. TSN was reported to inhibit the human oncogenic phenotype of gastric cancer via miR-200a/β-catenin axis.…”
Section: Introductionmentioning
confidence: 99%